Self-acceptance, Coping Strategies and Depression on Street Children - Athiyallah, Arina; Kurniawati, Rafidhah; Karuniasari, Zulfanida; Setyarini, Maya; Purwandari, Eny (International Journal of Psychosocial Rehabilitation, 2020)
Street children face depression, yet little is known contributing to what extend the depression is related to self-acceptance and coping strategies. The research was quantitative correlational study and the aim of the present research is to determine the degree to which a relationship exists between self-acceptance, coping strategies and depression on street children. A total of 50 street children who are living on and living off street ranging from 10-25 years old were recruited by using convenience sampling. This study assessed depression (Beck’s Depression Inventory), Self-Acceptance Scale, and Coping Strategies Scale in the participants. Linear regression was administered to examine the associations between self-acceptance, coping strategies and depression on street children. The result of the study is the result of the study is depression level mean 10.28 which categorized as normal, while the regression coefficient scores there is a negative correlation between self-acceptance, coping strategies and depression on street children however there is no significant correlation between three variables.